Pertanggungjawaban Pidana Pencemaran Teluk Balikpapan oleh Nahkoda Kapal Mv Ever Judger Republik Rakyat China (Studi Putusan Pengadilan Negeri Balikpapan Nomor : 749/Pid.B/LH/2018/PN Bpp) - Tanjung, Wiranti; Ablisar, Madiasa; Mulyadi, Mahmud; Ekaputra, Mohammad (Sekolah Tinggi Ilmu Hukum Graha Kirana, 2023)
AbstractThe incident of environmental pollution and destruction in the Balikpapan Bay area which was caused by the breaking of the undersea crude oil distribution pipe belonging to PT Pertamina RU V Balikpapan appointed the Ship Master Mv. Ever Judger on behalf of Zhang Deyi as the perpetrator of the pollution who was then investigated and tried by the Balikpapan District Court. This research will examine criminal liability according to Law Number 32 of 2009 concerning Environmental Protection and Management, the form of responsibility for the pollution of Balikpapan Bay carried out by the captain of the ship Mv Ever Judger of the People's Republic of China as well as the urgency of corporate criminal responsibility for criminal acts of pollution of Balikpapan Bay. carried out by the captain of the ship Mv Ever Judger of the People's Republic of China (Study of Balikpapan District Court Decision Number: 749/Pid.B/LH/2018/PN Bpp). This research will use a type of normative legal research using secondary data consisting of primary, secondary and tertiary legal materials, which are then analyzed using qualitative descriptive analysis. Criminal liability for perpetrators of environmental pollution according to Law Number 32 of 2009 concerning Environmental Protection and Management is based on the principle of no crime without fault, the captain of the ship Mv Ever Judger is held accountable as the sole perpetrator of violating Article 98 Paragraph (3) of the Law of the Republic of Indonesia Number 32 of 2009 concerning Environmental Protection and Management and sanctions are given in the form of imprisonment and fines. In the case of environmental pollution in Balikpapan Bay, the parties that can be held responsible should not only be individuals, but also corporations such as the company that owns the ship Mv. Ever Judger because it has a causal relationship between the defendant's actions between the giver of the order and the executor of the order which is actually regulated in articles 116 to 118 of the UUPPLH.AbstrakKejadian pencemaran dan perusakan lingkungan di wilayah Teluk Balikpapan yang disebabkan oleh terputusnya pipa penyaluran minyak mentah di bawah laut milik PT Pertamina RU V Balikpapan menetapkan Nakhoda Kapal Mv. Ever Judger atas nama Zhang Deyi sebagai pelaku yang kemudian diperiksa dan di adili Pengadilan Negeri Balikpapan. Penelitian ini menggunakan jenis penelitian hukum normatif dengan menggunakan data sekunder yang terdiri dari bahan hukum primer, sekunder dan tersier, yang kemudian di analisa dengan menggunakan analisa deskriptif kualitatif. Pertanggungjawaban pidana pelaku pencemaran lingkungan hidup menurut Undang-undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup di dasarkan pada asas tiada pidana tanpa kesalahan, terhadap kasus pencemaran Teluk Balikpapan, nahkoda kapal Mv Ever Judger dimintai pertanggungjawaban sebagai pelaku tunggal melanggar Pasal 98 Ayat (3) Undang-undang Republik Indonesia Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup dan diberikan sanksi dalam bentuk pidana penjara dan denda. Seharusnya kasus pencemaran lingkungan hidup teluk Balikpapan, pihak yang dapat dimintai dipertanggungjawabkan tidak hanya perorangan saja, tetapi juga korporasi seperti badan perusahaan pemilik kapal Mv. Ever Judger oleh karena memiliki relasi kausalitas dari perbuatan terdakwa antara si pemberi perintah dengan pelaksana perintah yang sebenarnya telah di atur dalam pasal 116 sampai dengan pasal 118 UUPPLH.